SOCIO-CULTURAL CHANGES IN UKRAINE AT THE BEGINNING OF THE 21ST CENTURY AND THEIR IMPACT ON THE FUNCTIONING OF THE THEATER - Слуцький, Віталій (SWorldJournal, 2024)
театр, український театр, соціокультурні зміни, глобалізація